The Moderating Role of Environmental Knowledge in Green Halal Cosmetic Purchase Intentions - Herianto; Wardani, Tri Ulfa; Purnamasari, Dian Septi; Haslindah (Universitas Airlangga, 2025)
The purpose of this study was to identify and analyze the purchase intention of environmentally friendly halal cosmetic products by millennial Muslim generations in Indonesia moderated by knowledge of the environment. This study used a quantitative approach, data were obtained by distributing questionnaires (google form) through WhatsApp and Instagram social media, sampling using a perceptive sampling technique, the number of respondents was 115 people with the withdrawal of the younger generation of women and men aged 15-30 years and living in Indonesia. The research model uses the structural equation modeling–partial least structural (SEM) model with the help of Smart-PLS 3 statistical software analysis. The findings of this study indicate that self-efficacy influences attitudes, eco-label influences halal-green awareness, normative belief variables influences on subjective norms, perceptual behavioral control influences the intention to consume environmentally friendly halal. Furthermore, the presence of environmental knowledge as a moderating variable indicates that this variable does not have a moderating effect on the relationship between attitude variables, green-halal awareness and subjective norms with the intention to consume environmentally friendly halal. However, these variables have a significant direct effect on the intention to consume environmentally friendly halal. This study is one of the comprehensive research on the intention to buy environmentally friendly halal products.